2010
DOI: 10.1111/j.1365-2966.2010.17425.x
|View full text |Cite
|
Sign up to set email alerts
|

Outburst activity in comets - II. A multiband photometric monitoring of comet 29P/Schwassmann-Wachmann 1

Abstract: We have carried out a continuous multiband photometric monitoring of the nuclear activity of comet 29P/Schwassmann–Wachmann 1 from 2008 to 2010. Our main aim has been to study the outburst mechanism on the basis of a follow‐up of the photometric variations associated with the release of dust. We have used a standardized method to obtain the 10‐arcsec nucleus photometry in the V, R and I filters of the Johnson–Kron–Cousins system, which are accurately calibrated with standard Landolt stars. The production of du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 25 publications
5
47
1
Order By: Relevance
“…Furthermore, some dust outbursts may overlap in time, which may be the case for the outburst A. Thus, as Trigo-Rodríguez et al (2010) points out, the ∼ 50 day average obtained from an observed 7 outbursts/year may not be physically tied to the actual rotation rate of the nucleus.…”
Section: Co and Dust Outburstsmentioning
confidence: 99%
“…Furthermore, some dust outbursts may overlap in time, which may be the case for the outburst A. Thus, as Trigo-Rodríguez et al (2010) points out, the ∼ 50 day average obtained from an observed 7 outbursts/year may not be physically tied to the actual rotation rate of the nucleus.…”
Section: Co and Dust Outburstsmentioning
confidence: 99%
“…This continuous activity, often called its "quiescent" activity, is believed to be driven by sublimation of the supervolatile CO (Festou et al (2001); Gunnarsson et al (2002); Paganini et al (2013)) and/or from gases released during the crystallization of amorphous water ice (Jewitt (2009) ;Womack et al (2017)). (3) Additionally, it frequently, and consistently, undergoes major outbursts events in activity with estimated lower-limits for the total mass of material ejected on the order of 10 8 − 10 9 kg per outburst event (Trigo-Rodríguez et al (2010); Kossacki & Szutowicz (2013); Hosek et al (2013); Miles et al (2016); Schambeau et al (2017)). These outburst events are detected as corresponding increases in surface brightness of the coma's dust continuum features and range over several orders of magnitude, lasting from several days to a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…
As far as outbursts activity is concerned, the 29P/Schwassmann-Wachmann 1 is the exceptional comet. This Centaur object shows quasi-regular flares with periodicities of 50 days (Trigo-Rodriguez et al 2010). In the introductory part of the presented paper the most well-known hypotheses which try to explain this cometary behaviour are reviewed.
…”
mentioning
confidence: 90%
“…Therefore, 29P/SW1 is also a Centaur object as far as its orbit is concerned. Secondly, despite the relatively large distance from the Sun, the comet shows an unexpected outburst activity with a periodicity of, on the average, 50 days (Trigo-Rodriguez et al 2010).…”
Section: The Outbursts Of the 29p/sw1mentioning
confidence: 99%